Nature of ferroelectric to paraelectric phase transition in multiferroic 0.8 BiFeO3-0.2Pb (Fe1/2Nb1/2)O3 ceramics - Patel J.P.; Singh A.; Pandey D. (My University, 2025)
We present here the results of high temperature powder x-ray diffraction study on 0.8 BiFeO3 -0.2Pb (Fe1/2 Nb1/2) O3, which is isostructural with the well known multiferroic BiFeO3 (BF). It is shown that the room temperature ferroelectric phase of 0.8BF-0.2PFN in the R3c space group transforms to the paraelectric/paraelastic cubic (Pm3-m) phase directly without any intermediate " Β " phase reported in the literature for pure BF. This transition is of first order type as confirmed by the coexistence of R3c and Pm3- m phases over a 100 K range and discontinuous change in the unit cell volume. © 2010 American Institute of Physics.